(untitled) (Research, Society and Development, 2022)
This paper presents the results of a pedagogical practice which was applied in a 4th grade elementar school class of a public school in the municipality of Conceição da Barra - ES. The pedagogical proposal was carried out during the discipline Production of Pedagogical Artifacts in Sciences, offered by the Postgraduate Course Teaching in Basic Education, of Federal University of Espírito Santo (UFES), and aimed to produce a pedagogical artifact based on a track game which was used as a didactic resource to promote the participation, interest and fixation of the themes homogeneous and heterogeneous mixtures and methods of separation of mixtures. In addition, we sought to verify applicability of the didactic game, inserting the playful as a tool to improve the learning teaching process. The pedagogical practice was carried out in 3 stages. In the first stage, a theoretical/practical class approached the proposed theme was held. The second stage was characterized by the application of the game and the third stage was related to the application of the questionnaire to evaluate the didactic game, based on the perception of the students. Throughout the pedagogical intervention, the students were curious, questioning and enthusiastic about the activities that were proposed. As such, it is extremely importante to develop diversified pedagogical practices with the aim of contributing to the students being more participatory, motivated and, moreover, that they can significantly achieve learning.